2021
DOI: 10.1371/journal.pone.0254633
|View full text |Cite
|
Sign up to set email alerts
|

Trends in COVID-19 case-fatality rates in Brazilian public hospitals: A longitudinal cohort of 398,063 hospital admissions from 1st March to 3rd October 2020

Abstract: Background Almost 200,000 deaths from COVID-19 were reported in Brazil in 2020. The case fatality rate of a new infectious disease can vary by different risk factors and over time. We analysed the trends and associated factors of COVID-19 case fatality rates in Brazilian public hospital admissions during the first wave of the pandemic. Methods A retrospective cohort of all COVID-19-related admissions between epidemiological weeks 10–40 in the Brazilian Public Health System (SUS) was delimited from available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
(39 reference statements)
5
16
0
1
Order By: Relevance
“…In Brazil, three large population-based studies including 522,167 [age 61 (IQR 47–73) years], 254,288 (age 60 ± 17 years) (232,036 of whom had a defined outcome), and 228,196 [age 61 (IQR 48–73) years] COVID-19 patients reported 30.7% 8 , 38% 4 and 37% 6 in-hospital mortality, respectively, whereas two smaller cohorts (mean/median ages not reported) of 46,285 and 11,321 in-hospital patients (6882 of whom had a defined outcome) found much higher mortality rates of 46.2% 9 and 47.3% 7 , respectively (Supplementary Table 10 ). None of these studies, however, discriminated the in-hospital mortality between public and private hospitals 4 , 6 10 . In fact, a lower (24.4%) in-hospital mortality was found in a cohort of 89,405 patients (age 58.9 ± 16.8 years) attended exclusively by the Brazilian unified public healthcare system 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, three large population-based studies including 522,167 [age 61 (IQR 47–73) years], 254,288 (age 60 ± 17 years) (232,036 of whom had a defined outcome), and 228,196 [age 61 (IQR 48–73) years] COVID-19 patients reported 30.7% 8 , 38% 4 and 37% 6 in-hospital mortality, respectively, whereas two smaller cohorts (mean/median ages not reported) of 46,285 and 11,321 in-hospital patients (6882 of whom had a defined outcome) found much higher mortality rates of 46.2% 9 and 47.3% 7 , respectively (Supplementary Table 10 ). None of these studies, however, discriminated the in-hospital mortality between public and private hospitals 4 , 6 10 . In fact, a lower (24.4%) in-hospital mortality was found in a cohort of 89,405 patients (age 58.9 ± 16.8 years) attended exclusively by the Brazilian unified public healthcare system 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, COVID-19 is widely distributed across Brazil’s 5 macro-regions (North, Northeast, Central-West, Southeast, and South) with not only a high incidence, but also a high, albeit uneven, in-hospital mortality, which likely relates in part to the existing regional discrepancies of the country’s healthcare system 4 . Previous studies, which combined account for ≥ 1 million patients hospitalized due to COVID-19 in Brazil, have reported mortality rates ranging from 21.7 to 47.3% 4 , 6 10 . All of these studies, however, originated from “SIVEP-Gripe”—the main Brazilian Ministry of Health’s (BMH) repository of notifications of COVID-19 hospitalizations—and none of them discriminated the in-hospital mortality between public and private institutions 4 , 6 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil witnessed a widespread distribution of COVID-19 across all regions and was most severely affected by the pandemic 8 , 9 . Almost 200,000 COVID-19 deaths were reported just in 2020 10 . The country started vaccination campaigns against COVID-19 on January 17 th , 2021, prioritizing health workers, older adults (starting at age 85 and gradually vaccinating younger age groups), indigenous populations, and institutionalized individuals 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The results differed in a systematic review of 33 studies of other countries, which showed a CFR of 17.1% among hospitalized patients [ 23 ]. In Brazil, the CFR trend even showed a decline in the overall hospital CFR of COVID-19 with a minimum value of 20% [ 24 ]. A similar downward trend was observed in studies of hospitalized patients in Spain and United States [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%